Strategies for Community Education Prior to Clinical Trial Recruitment for a Cervical Cancer Screening Intervention in Uganda - Mitchell, Sheona M.; Pedersen, Heather N.; Sekikubo, Musa; Biryabarema, Christine; Byamugisha, Josaphat J. K.; Mwesigwa, David; Steinberg, Malcolm; Money, Deborah M.; Ogilvie, Gina S. (Frontiers in Oncology, 2016)
Introduction: Community engagement and education can improve acceptability and participation in clinical trials conducted in Kisenyi, Uganda. In preparation for a randomized controlled trial exploring different methods for cervical cancer screening, we explored optimal engagement strategies from the perspective of community members and health professionals. Methods: We conducted key informant interviews followed by serial community forums with purposeful sampling and compared the perspectives of women in Kisenyi (N=26) to healthcare workers (HCW) at the local and tertiary care center levels (N=61) in a participatory, iterative process. Results: Key themes identified included format, content, language, message delivery and target population. Women in Kisenyi see demonstration as a key part of an educational intervention and not solely a didactic session whereas health professionals emphasized the biomedical content and natural history of cervical cancer. Using local language and lay leaders with locally accessible terminology was more of a priority for women in Kisenyi than clinicians. Simple language with a clear message was essential for both groups. Localization of language and reciprocal communication using demonstration between community members and HCW was a key theme. Conclusions: Although perceptions of the format are similar between women and HCW, the content, language and messaging that should be incorporated in a health education strategy differ markedly. The call for lay leaders to participate in health promotion is a clear step towards transforming this cervical cancer screening project to be a fully participatory process. This is important in scaling-up cervical cancer screening programs in Kisenyi and will be central in developing health education interventions for this purpose.